Penerapan Metode Tasmi’ dalam Meningkatkan Hafalan Al -Qur’an Santriwan Kelas 10 di Asrama MAN 3 Palembang - Muhammad Yuchdi Prasetya; Sri Maryati; Fajri Ismail (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
This research analyzes the effectiveness of the Tasmi' method in improving class 10 students' memorization of the Al-Qur'an in the MAN 3 Palembang dormitory. Previously, the tahfidz program still used the sorogan method which was similar to quantitative method with an experimental design, where students are given a pre-test before implementing the Tasmi' method and a post-test afterward. Data was collected through an oral memorization test. The pre-test results showed that the students' memorization scores ranged from 5.67 to 7.33 with an overall average of 6.36. After implementing the Tasmi' method, the post-test results showed a significant improvement with an average score between 6.67 to 7.67 and an overall average of 6.91. These findings show that the Tasmi' method is effective in improving students' memorization of the Al-Qur'an, especially in the aspects of accuracy, fluency and consistency. Thus, this method can be a more effective alternative in the tahfidz program in the dormitory environment.